Professional C♯ 2012 and .Net 4.5 - Nagel, Christian, 1965- (Programmer to programmer., 2013)
Intermediate to advanced technique coverage, updated for C♯ 2012 and .NET 4.5This guide is geared towards experienced programmers looking to update and enhance their skills in writing Windows applications, web apps, and Metro apps with C♯ and .NET 4.5. Packed with information about intermediate and advanced features, this book includes everything professional developers need to know about C♯ and putting it to work. Covers challenging .NET features including Language Integrated Query (LINQ), LINQ to SQL, LINQ to XML, WCF, WPF, Workflow, and Generics Puts the new Async keyword to work and feature.